2015
DOI: 10.1186/s13075-015-0902-0
|View full text |Cite
|
Sign up to set email alerts
|

Soluble biglycan: a potential mediator of cartilage degradation in osteoarthritis

Abstract: BackgroundSoluble biglycan (sBGN) and soluble decorin (sDCN), are two closely related essential components of extracellular matrix which both have been shown to possess proinflammatory properties. We studied whether sBGN or sDCN were present in synovial fluid (SF) of osteoarthritis (OA) or rheumatoid arthritis (RA) patients and studied sBGN or sDCN potential role in the degradation of OA cartilage.MethodsSF obtained from meniscus tear, OA, and RA patients were analysed for sBGN and sDCN using enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 50 publications
1
51
0
1
Order By: Relevance
“…As described earlier in this narrative, cartilage extracellular matrix fragments such as biglycan, fibronectin, aggrecan and low molecular weight hyaluronan stimulate cell types in the joint via PRRs, leading to the production of inflammatory mediators and the attraction of inflammatory cells, and as such act as alarmins [34][35][36][37]93]. Moreover, they are taken up by synovial macrophages, resulting in the activation of proinflammatory responses in these cells.…”
Section: Alarmins In Osteoarthritismentioning
confidence: 99%
“…As described earlier in this narrative, cartilage extracellular matrix fragments such as biglycan, fibronectin, aggrecan and low molecular weight hyaluronan stimulate cell types in the joint via PRRs, leading to the production of inflammatory mediators and the attraction of inflammatory cells, and as such act as alarmins [34][35][36][37]93]. Moreover, they are taken up by synovial macrophages, resulting in the activation of proinflammatory responses in these cells.…”
Section: Alarmins In Osteoarthritismentioning
confidence: 99%
“…Here, it might play a role in promoting alignment or in stabilizing such an organization, thereby creating a matrix capable of withstanding load-bearing forces [35]. The slightly decreased COMP expression and the increased pericellular and territorial decorin synthesis demonstrate degeneration-related catabolic changes as described earlier for articular chondrocytes [36,37]. COMP is a target of matrix metalloproteinases, including MMP-13 [38], which have been shown to be upregulated in chondrogenically differentiating mesenchymal stem cells as well as in cardiofibroblasts by targeting the β2-AR [18,39].…”
Section: Discussionmentioning
confidence: 79%
“…The observed presence of intracellular staining might indicate a compensatory effort of the chondrocytes to restore the overall proteoglycan content occurring as a result of the ongoing tissue damage 44 . Moreover, Barreto et al 45 showed that biglycan effectively induces the upregulation of proteinase in early OA stage (stage I), but that this effect is lower in advanced OA stages (stage VI), a condition in which most of the PCM components have already suffered from degradation. As in our ELISA, total biglycan protein content has been shown in radioimmunoassays to be reduced in osteoarthritic cartilage 21 …”
Section: Discussionmentioning
confidence: 99%